824 MOLECULAR UNDERPINNINGS OF NEUROENDOCRINE DIFFERENTIATION IN ESOPHAGEAL ADENOCARCINOMA AND ITS PROGNOSTIC SIGNIFICANCE. (17th September 2021) - Wilson, G; Elimova, E; Yeung, J; Darling, G; N Kalimuthu, S
Abstract: : The presence of neuroendocrine (NE) differentiation has been previously reported in both morphological subtypes, (intestinal and diffuse), of esophageal adenocarcinoma, (EAC). This is more commonly seen in the post-treatment setting and is thought to confer a more aggressive phenotype. However, the molecular underpinning and therapeutic implications of NE differentiation within EAC is poorly understood. Herein, the goal is to understand the molecular mechanisms, evolution and the prognostic significance of NE development in EAC tumours. Methods: We interrogated a previously published transcriptome dataset with matched H&E slides, TCGA EAC (N = 86). Moreover, we have begun reviewing H&E slides from EAC patients from UHN (N = 50). We created a NE gene expression signature (N = 25 genes) from the literature as an initial proof of concept. We quantified the presence of a NET-like/organoid morphology in the matched H&E slides and correlated it with the average z-score of the NE gene signature calculated from the matched transcriptome data. Results: NE differentiation was present in 27/86 cases with a mean of 21.01% +/− 20.9 within the tumour area. We compared the expression of our NE gene signature with the proportion of NE morphology and observed a moderate correlation between morphology with the gene expression (R^2 = 0.546, P < 0.001 ordinary least squares regression), providing validation that the organoid/NET-like morphological pattern correlates with NE differentiation. Furthermore, we have validated the presence of NE morphology in a subset of the UHN samples using electron microscopy and immunohistochemistry (chromogranin and synaptophysin). Conclusion: This is a first of a kind study to profile a specific morphology with a transcriptional signature within EAC across a large cohort of patient samples. Correlation of NE-features with clinical outcome together with treatment resistant implications is currently underway.